Volga Kalmyks and Kazakhs, Eighteenth – Early Nineteenth Centuries: More on the Evolution of Their Relations - Kadyrbayev Alexander Sh. (Oriental Studies, 2023)
Introduction. The paper introduces some newly discovered archival material and sources in different languages to examine the shaping of Kalmyk-Kazakh relations in the eighteenth and early nineteenth centuries. The concern about the issue is explained by its limited historiography, since only a few unconnected works have tackled it to date. Furthermore, decent research efforts therein do imply the need for interdisciplinary and cross-civilizational/cross-cultural approaches. Goals. The work attempts a comprehensive review of how relations between the Volga Kalmyks and Kazakhs developed throughout the mentioned period, which shall shed light on the dramatic events that would prove crucial to historical destinies of the nomadic peoples. Materials. To facilitate this, the publication introduces some related data contained in various sources (repositories) and supplemented with historiographic analyses by both Russian and foreign scholars. The identified period seems most instrumental in analyzing the evolution of Kalmyk-Kazakh relations and the latter’s impacts onto their then (and subsequent) historical agendas. Results. In the eighteenth and early nineteenth centuries, relations between the Volga Kalmyks and Kazakhs were somewhat controversial and ambivalent, which never excluded certain cultural ties then manifested in bilingualism of Kazakh elites that tended to make fluency in Kalmyk a useful rule of theirs, in dynastic marriages and mutual judicial influences traced in codes of laws (Jeti-Jargy and Iki Tsaadzhin Bitchig).